DOTHIEPIN, QT PROLONGATION AND TORSADES DE POINTES - Andrade, Chittaranjan (Medknow Publications, 1999)
A case is reported of electrocardiographic QT prolongation that was presumbty familial in origin. Torsades de points developed in association with the use ofdothinepin, despite the pmscription of a low dose of this drug.